REASONING OF THE SOWING TIME AND THE DEPTH OF SEEDING FOR THE MANAGEMENT OF THE PRODUCTION PROCESS AND THE CROP CAPACITY OF BEAN VARIETIES IN THE CONDITIONS OF THE RIGHT-BANK FOREST-STEPPE OF UKRAINE - Овчарук, О. В.; Овчарук, О. В.; Степась, А. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
Here reviewed the researches’ results of highly productive varieties of common beans; the productivity formation depending on the sowing time and the seeding depth in the conditions of the Right-Bank Forest Steppe. The researches’ results established the dependence of the plant productivity on the varietal characteristics of kidney beans; sowing time and the depth of seeding. The biggest number of beans per plant were found from the early-spring period (20-25. IV) in Perlyna variety – 24;5; Nadia variety – 23;3; Nespodivanka variety – 22;4. The smallest number of beans per plant was formed by varieties of Mavka – 20;6; Schedra – 19;7 and Bukovynka – 19;7. The lowest rates of the bean formation per plant have the summer period of sowing (1-5.VI). For different varieties it is: Nadia – 11;8; Schedra – 12;0; Bukovynka – 12;3; Nespodivanka – 12;4; Mavka – 12;5 and Perlyna – 12;6 beans per plant. This difference in numbers of the bean formation per plant for the summer period of sowing is confirmed by the lack of the available soil moisture. The highest yield was received from the variant with the second sowing term (1-5. V) that totalled; respectively; 2;96; 2;87 and 2;31 t/ha. For the Mavka and Nespodivanka varieties the third sowing term (15-20. V) was better for the realization of productivity. During it was received yield of kidney beans 2;84 and 2;37 t/ha; respectively. For the Perlyna variety the highest yield was received from the first sowing term (15-20. IV) – 2;85 t/ha. Comparing the productivity of different varieties depending on the sowing terms it should also be noted that the summer period (1-5.VI) was characterized by the lowest numbers of the crop capacity of all studied varieties: Bukovynka – 1;89; Nadia – 1;81; Mavka – 1;81; Perlyna – 1;61; Nespodivanka – 1;59; Schedra – 1;40 t/ha.